The Book of Psalms in the works of J. G. Herder: research, translation, reception in poetry - Sinilo, Galina V. (Journal of the Belarusian State University. Philology, 2021)
In this paper we explore the reception of the Book of Psalms in the work of J. G. Herder (1744 –1803), an outstanding German philosopher, theologian, biblical scholar, folklorist, translator and poet. We affirm that Herder discovers and substantiates a fundamentally new approach to the Bible as an artistic phenomenon, as the result of the work of the Jewish people at the stage of Antiquity. The discoverer of the cultural-historical approach to art and the comparative study of literatures, Herder views the Bible not only as Holy Scripture, carrying eternal truths, but also as poetry, born in a specific socio-cultural context. In the monumental work «On the spirit of Hebrew poetry» («Vom Geist der Ebräischen Poesie», 1782–1783), he gives a historical and cultural overview of the emergence and development of Jewish religion and poetry, shows biblical poetry, on the one hand, as an organic part of the world literary process, on the other hand, its uniqueness in comparison with other ancient literatures. Rethinking the concept of «classical literature» (and, more broadly, «classical culture»), Herder speaks of the need to include in the orbit of the «classical» ancient oriental cultures and especially the Bible, which had a huge impact on European culture and its poetry. At the same time, he asserts the impossibility of evaluating biblical poetry according to the criteria of Hellenic poetry, like any other. Among the biblical books, Herder is especially attracted by the Book of Psalms, which is an anthology of Hebrew religious, philosophical and liturgical lyrics. He rightly considers it the highest rise of Jewish and world poetry, because it presents the widest range of feelings of a deeply religious person, striking in its depth the picture of the human soul, conducting a dialogue with God. Moreover, for Herder, it is an example of a truly «naïve» poetry pouring out directly from the heart. He examines the biblical psalms in a historical and cultural context, emphasises the author’s principle in them, reveals their genre specificity and peculiarities of their stylistics. In his research, Herder cites his own numerous translations of the psalms and for the first time develops the scientific principles of literary translation, based on the original, accurately conveying not only the meaning, but also the form of the work, its rhythm melodies and stylistics. It is shown that in the religious and philosophical poetry of Herder himself the Book of Psalms plays a decisive archetextual role, performing the functions of meaning and text generation. The style of the biblical psalms is especially important for the Stürmer period of Herder’s work, but in general, their spiritual meanings feed all of his religious and philosophical lyrics. It is argued that the rhythm and style of biblical psalms influences the formation of the genre of a religious and philosophical hymn, written in free rhythms (in freien Rhythmen), that is, vers libre, and first mastered by F. G. Klopstock. The same genre is the leading one in Herder’s religious and philosophical lyrics. Thus, the psalms also become architects (genre samples) for his poetry. In general, both Herder’s biblical studies and his poetry, archetextually associated with the Book of Psalms, represent a synthesis of theology, literary criticism, cultural philosophy and poetry itself.
Keywords: J. G. Herder; the Bible; the Book of Psalms; reception; archetext; archetextuality; cultural philosophy; cultural and historical school; literary translation; religious and philosophical lyrics; religious and philosophical hymn in free rhythms